Aetiology of pleural effusion among patients with chronic kidney disease - Afroz, Farhana; Hossain, Mohammad Delwar (BIRDEM Medical Journal, 2025)
Background: Pleural effusion is common in patients with chronic kidney disease (CKD). Aetiology of pleural effusion is diverse like heart failure, tuberculosis (TB), pneumonia, uraemia etc. Proper diagnosis of the cause is necessary as treatment plan varies from case to case. This study was designed to evaluate the aetiology of pleural effusion in patients with CKD. Methods: This cross-sectional study was conducted in the Departments of Nephrology and Dialysis, Internal Medicine and Respiratory Medicine of BIRDEM General Hospital, Dhaka, from July to December, 2022. Sixtytwo patients, aged e_18 years with CKD stage 3 to 5 with pleural effusion were included in this study. Patients having bleeding disorder, recent myocardial infarction or patients unwilling for thoracocentesis were excluded. Patients were evaluated clinically and by aspiration of pleural fluid. Results: Of the 62 patients, 42 (67.7%) were male and 20 (32.3%) were female. The mean age was 52 years. Commonest symptom was dyspnea (47, 75%), cough (33, 53%), weight loss (23, 37%) anorexia (22, 35%), fever (16, 25%), pleuritic chest pain (15, 24%), bilateral basal crepitations (15, 24%), abdominal swelling (9, 14%), engorged neck veins (7, 11%). Diabetes mellitus (DM) (50, 80%) was the commonest comorbidity in our patients. A previous history of TB was present in 9 (14%) patients (most of whom completed treatment) and 7 patients had history of malignancy (including 2 on treatment). In our study, 38 (61%) patients were in CKD stage 4, 6 (9%) patients were on dialysis. In most cases (51, 81%), effusions were bilateral transudative. Fluid overload (32, 62%), heart failure (29, 56%) and nephrotic syndrome (11/21%) were common transudative effusion. Etiology of exudative pleural effusion were TB, uremia, empyema and hypothyroidism. Conclusion: Aetiologiy of pleural effusion in CKD are mostly fluid overload, heart failure, nephrotic syndrome, TB and empyema. BIRDEM Med J 2025; 15(1): 39-43